The miR-17-92 cluster counteracts quiescence and chemoresistance in a distinct subpopulation of pancreatic cancer stem cells. Issue 12 (17th April 2015) - Cioffi, Michele; Trabulo, Sara M; Sanchez-Ripoll, Yolanda; Miranda-Lorenzo, Irene; Lonardo, Enza; Dorado, Jorge; Reis Vieira, Catarina; Ramirez, Juan Carlos; Hidalgo, Manuel; Aicher, Alexandra; Hahn, Stephan; Sainz, Bruno; et al.
Abstract : Objective: Cancer stem cells (CSCs) represent the root of many solid cancers including pancreatic ductal adenocarcinoma, are highly chemoresistant and represent the cellular source for disease relapse. However the mechanisms involved in these processes still need to be fully elucidated. Understanding the mechanisms implicated in chemoresistance and metastasis of pancreatic cancer is critical to improving patient outcomes. Design: Micro-RNA (miRNA) expression analyses were performed to identify functionally defining epigenetic signatures in pancreatic CSC-enriched sphere-derived cells and gemcitabine-resistant pancreatic CSCs. Results: We found the miR-17-92 cluster to be downregulated in chemoresistant CSCs versus non-CSCs and demonstrate its crucial relevance for CSC biology. In particular, overexpression of miR-17-92 reduced CSC self-renewal capacity, in vivo tumourigenicity and chemoresistance by targeting multiple NODAL/ACTIVIN/TGF-β1 signalling cascade members as well as directly inhibiting the downstream targets p21, p57 and TBX3. Overexpression of miR-17-92 translated into increased CSC proliferation and their eventual exhaustion via downregulation of p21 and p57. Finally, the translational impact of our findings could be confirmed in preclinical models for pancreatic cancer. Conclusions: Our findings therefore identify the miR-17-92 cluster as a functionally determining family of miRNAs in CSCs, and highlight the putative potential of developing modulators of this cluster to overcome drug resistance in pancreatic CSCs.